Discoverability in digital repositories : systems, perspectives, and user studies - Woolcott, Liz; Shiri, Ali, 1968- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
"While most discoverability evaluation studies in the Library and Information Science field discuss the intersection of discovery layers and library systems, this book looks specifically at digital repositories, examining discoverability from the lenses of system structure, user searches, and external discovery avenues. Discoverability, the ease with which information can be found by a user, is the cornerstone of all successful digital information platforms. Yet, most digital repository practitioners and researchers lack a holistic and comprehensive understanding of how and where discoverability happens. This book brings together current understandings of user needs and behaviors and poses them alongside a deeper examination of digital repositories around the theme of discoverability. It examines discoverability in digital repositories from both user and system perspectives by exploring how users access content (including their search patterns and habits, need for digital content, effects of outreach, or integration with Wikipedia and other web-based tools) and how systems support or prevent discoverability through the structure or quality of metadata, system interfaces, exposure to search engines or lack thereof, and integration with library discovery tools. Discoverability in Digital Repositories will be particularly useful to digital repository managers, practitioners, and researchers, metadata librarians, systems librarians, and user studies, usability and user experience librarians. Additionally, and perhaps most prominently, this book is composed with the emerging practitioner in mind. Instructors and students in Library and Information Science and Information Management programs will benefit from this book that specifically addresses discoverability in digital repository systems and services"--
Part 1: Digital repository functionality -- Digital repositories and discoverability: Definitions and typology / George Macgregor -- Understanding repository functionality and structure / Sharon Farnel -- Understanding the role of metadata in a digital repository / Jenn Riley -- Understanding linked data and the potential for enhanced discoverability / Anna Neatrour, Teresa K. Hebron -- User search behavior in digital repositories / Oksana L. Zavalina, Mary Burke -- Part 2: Case studies in visibility and discoverability outside the digital repository -- Discoverability within the library: Integrated systems and discovery layers / JoLinda Thompson, Sara Hoover -- Discoverability beyond the library: Wikipedia / Elizabeth Joan Kelly -- Discoverability and search engine visibility of repository platforms / Danping Dong, Chee Hsien Aaron Tay.
OCLC-licensed vendor bibliographic record.
Keywords: Institutional repositories; Digital libraries; Electronic information resource searching; COMPUTERS / Management Information Systems